The dietary treatment of histamine intolerance reduces the abundance of some histamine-secreting bacteria of the gut microbiota in histamine intolerant women. A pilot study - Sánchez-Pérez, Sònia; Comas-Basté, Oriol; Duelo, Adriana; Veciana-Nogués, M. Teresa; Berlanga, Mercedes; Vidal-Carou, M. Carmen; Latorre-Moratalla, M. Luz (Frontiers in Nutrition, 2022)
Restrictive diets for the treatment of different gastrointestinal disorders are reported to change the composition of intestinal microbiota. Recently, it has been proposed that individuals with histamine intolerance suffer from intestinal dysbiosis, having an overabundance of histamine-secreting bac-teria, but how it is still unknown this state is affected by the usual dietary treatment of histamine intolerance (i.e. low-histamine diet and the supplementation with diamine oxidase enzyme). Thus, a preliminary study was carried out aiming to evaluate the potential changes on the composition of the intestinal microbiota in a group of five women diagnosed with histamine intolerance undergoing nine months of the dietary treatment of histamine intolerance. After sequencing bacterial 16S rRNA genes (V3-V4 region) and analyzing the data using the EzBioCloud Database, we observed a reduction in certain histamine-secreting bacteria, including the genera Proteus and Raoultella and the specie Proteus mirabilis. Moreover, it was also observed an increase in Roseburia spp, a bacterial group frequently related to gut health. These changes could help to explain the clinical improvement experienced by histamine intolerant women underwent a dietary treatment.